Bully for you, Teddy Roosevelt! - Fritz, Jean.; Wimmer, Mike (New York : G.P. Putnam's, 1991)
Follows the life of the dynamic twenty-sixth president, discussing his conservation work, hunting expeditions, family life, and political career.
Includes bibliographical references (p. 122-123) and index.
Children's Catalog (Wilson)
Junior High School Library Catalog (Wilson)
Elementary School Library Collection (Bro-Dart)
6.8
3-6
Keywords: Roosevelt, Theodore, -- 1858-1919 -- Juvenile literature; Roosevelt, Theodore, -- 1858-1919.; Roosevelt, Theodore, -- 1858-1919.; Presidents -- United States -- Biography -- Juvenile literature; Presidents; Presidents -- United States -- Biography